The chromatographic separation of mangifera extract / Aimi Husna Ali... [et al.] - Ali, Aimi Husna; J Jalani, Kathleen; Abdul Wahab, Ibtisam; Mohsin, Hannis Fadzillah (Universiti Teknologi MARA, Negeri Sembilan, 2019)
The phytochemicals and biological properties of Mangifera species are documented. The main constituents of M. pajang include gallic, p-coumaric and ellagic acids. The fruits of M. pajang possess antioxidant, antibacterial and anticancer properties. The phenolic is mentioned as the compound that is responsible for the antioxidant property of M. pajang. In this study, the methanolic extraction of M. pajang and M. indica was performed. Based on thin layer chromatography (TLC), the presence of the phenolics in the samples could be confirmed. Comparative TLC was accomplished and the retention factor (Rf) of pyrogallol was recorded as 0.85. From the result, the TLC profiling of M. pajang and M. indica extracts were almost similar. In addition, the compounds of M. pajang extracts were analyzed from the 1 H-Nuclear Magnetic Resonance (NMR) spectroscopy. A mixture of ascorbic acid and a sugar moiety could be detected. On the other hand, the NMR signal for the metabolite of mangiferin was not observed. Therefore, the compound might not present in the sample.